The image of the man in the book “Balaghat Al Nisa” - an analytical study - Sadiq Abbas, Wasan (Journal of College of Education, 2022)
The paradoxical dialectic of this research lies in the fact that it presents a distorted picture of what we have done in literary and poetic studies from the side of the common pictorial representation of the female entity in what is imprinted on the conscious intellectual data on the masculine side, and regarding images inspired by the reality of the existential experience in everything related to the opposite sex. The opposite perspective in the vision realized here will put the woman in a position of praise after she was praised by the other, and in a way that is imbued with satisfactory merits after she was flirt with them, and has the courage to confront those in authority and control matters without fear or apprehension, and criticizing the negative aspects that point against her It is a valuable entity in order to put an end to the suffering of its sexes, and many aspects that have achieved women's presence and entering the field of representation and rhetorical representation.The research will take into account, through the analytical approach that will be taken, the details of the rhetorical picture drawn by the woman in her rhetorical products and the differentiation she achieved for her literary identity, through the systemic effects that brought her to the meaning she aspires to, so she adopted for that a clear and obedient sign that is far from complex in order to convey the content of her speech smoothly and easily to the audience of recipients.
Keywords: women's reports; man